2018
DOI: 10.3390/sports6030096
|View full text |Cite
|
Sign up to set email alerts
|

Sport Courage, Worry and Fear in Relation to Success of Alpine Ski Learning

Abstract: (1) Background: Individuals’ psychological traits can influence not just success in sport but also the ability to learn new motor skills. We investigated whether sport courage, worry and fear differ between alpine ski-naive and basic level skiers and how they affect ski learning. (2): A total of 337 students (249 ski-naive and 88 basic level) participated in research consisting of a four-part questionnaire and structured skiing program. (3) Results: For beginners, lower fear (r = −0.30, p < 0.01) and higher Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Regarding gender, it was observed that women are more prone to use protection than men (87.5% vs. 65.4%). These findings might be due to women are usually more afraid than men towards the sports practice [34][35][36], which produces a decrease in the self-efficacy of the activity, and consequently, reduces its control [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding gender, it was observed that women are more prone to use protection than men (87.5% vs. 65.4%). These findings might be due to women are usually more afraid than men towards the sports practice [34][35][36], which produces a decrease in the self-efficacy of the activity, and consequently, reduces its control [37].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, women could use protection to decrease their fear, and, consequently, their performance may get better. For men, the performance predictor is self-efficiency, and when it grows, the performance gets better [37].…”
Section: Discussionmentioning
confidence: 99%
“…Si bien el esquí alpino siempre se ha considerado un deporte minoritario y elitista, su práctica se popularizó a partir de la década de los 80 del siglo pasado, coincidiendo con el desarrollo del turismo, la concienciación sobre la conservación y disfrute de la naturaleza, y los beneficios de la práctica deportiva en la misma, constituyéndose en nuestra sociedad junto con otros deportes practicados en la naturaleza como un modelo alternativo al deporte tradicional (García et al, 2019). Actualmente, y desde el punto de vista recreativo, el esquí alpino es uno de los deportes de invierno más populares, contando con más de 400 millones de practicantes a nivel mundial (Cigrovski, Radman, Konter, Očić, y Ružić, 2018;Vanat, 2018). Huguet i Parellada (1992) definió el esquí como -uno de los deportes más completos que existen, ya que hace trabajar al cuerpo de forma general y combina diversos elementos como son la habilidad, la resistencia, la velocidad y la destreza.…”
Section: Introductionunclassified
“…Snowsports are conducted at high speeds in environments with different natural and constructed risks [ 1 ]. Due to the exponential increase of ski and snowboard practitioners during the last 20 years, and with 400 million skiers or snowboarders around the world [ 2 , 3 , 4 ], a rise of the registered injuries associated to winter sports might be expected [ 5 ].…”
Section: Introductionmentioning
confidence: 99%